Instagram as an educational tool for foreign language teachers’ education (Research, Society and Development, 2021)
This article analyses the use of the social network Instagram as a means of disseminating content on technology and education in order to assist the education of foreign language teachers. This work is yield of studies of the research group - Technologies for Communicative Teaching of Foreign Languages (TECLE) - of the Federal University of Ceará (UFC). It aims to present a social network included in a non-formal teaching context, capable of not only disseminating the group, but also proposing innovative methodologies for language teaching and disseminating relevant information for teachers’ inclusion in the digital culture. The adoption of such proposal is relevant because digital technology is increasingly present in educational practices, leading to the need for adaptation. The methodology adopted in the study is exploratory, through which weekly created and shared publications were analysed in light of the Technological Pedagogical Content Knowledge (TPACK) model. The results of the study point out the contribution of the social network Instagram in the initial and continuing education of foreign language teachers, promoting the integration among pedagogical, content and technological knowledge of these professionals.